Comparison of Refractive Results IOL Calculation Using the IV Generation Formulas in Cases of Previous Radial Keratotomy - O. V. Shilovskih; A. N. Ulyanov; M. V. Kremeshkov; E. M. Titarenko (Oftalʹmologiâ)
Purpose: Comparison of refractive results calculation of IOL optical power calculated with the IV-generation formula in patients after a previously performed radial keratotomy and to determine the relationship of these results to modern standards of error calculation of the IOL optical power in cases of age-related cataract surgery.Patients and methods. The study group consisted of patients after radial keratotomy caused by myopia and myopic astigmatism. Retrospectively data of 47 cases were analyzed (42 patients), 13 women and 29 men. The average age — 58.9 years (range 44 to 64 years). Patients were operated on the basis of the Ekaterinburg center of IRTC “Eye microsurgery” phacoemulsification through incisions not intersecting radial scars of the cornea. The calculation of the IOL optical power was performed according to IV generation formula: II Holladay (Iol consultant HicSoap Pro) and Olsen (PhacoOptics,) built-in software Scheimpflug camera Oculus Pentacam. The formula was chosen with calculation that it covers the whole spectrum range of optical cornea and front-back axle of all patients in this sample. Refractive outcome was taken into account in one month or more after surgery.Results. Refractive error in case of calculation with formula Holladay II ±0.50 diopter was in 74% cases; ±1.00 diopter — in 92%, the average refractive error in calculation with the IOL optical power was 0.5 ± 1,2 diopters. Refractive error in the calculation with the Olsen formula was ±0.50 diopters in 75%; ±1.00 diopter — in 90% cases, the average refractive error of calculation the IOL optical power was 0.4 ± 1.3 diopters.Сonclusions. Refractive results of calculating the optical power IOL in cases after radial keratotomy using the formula IV generation (Olsen — Phaco Optics and Holladay II — HicSoap Pro), provide achievement of modern standards of error in the calculation of IOLs.